Television, Video Game and Social Media Use Among Children with ASD and Typically Developing Siblings. - Mazurek, Micah; Wenstrup, Colleen (Journal of Autism & Developmental Disorders, 2013)
This study examined the nature of television, video game, and social media use in children (ages 8-18) with autism spectrum disorders (ASD, n = 202) compared to typically developing siblings (TD, n = 179), and relative to other activities. Parents completed measures assessing children's screen-based and other extracurricular activities. Children with ASD spent approximately 62 % more time watching television and playing video games than in all non-screen activities combined. Compared with TD siblings, children with ASD spent more hours per day playing video games (2.4 vs. 1.6 for boys, and 1.8 vs. 0.8 for girls), and had higher levels of problematic video game use. In contrast, children with ASD spent little time using social media or socially interactive video games.